2020
DOI: 10.31004/basicedu.v4i2.332
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Media Gambar Terhadap Hasil Belajar Ipa Pada Siswa Sekolah Dasar

Abstract: Penelitian ini dilaksanakan di Gugus II Kecamatan Lemahabang, Kabupaten Karawang, dan penelitian di fokuskan pada siswa kelas V Tahun ajaran 2018/2019. Tujuan penelitian ini untuk mengetahui pengaruh media gambar terhadap hasil belajar IPA. Penelitian ini di latarbelakangi oleh rendahnya hasil belajar siswa terutama pada pelajaran IPA. Jenis Penelitian ini adalah penelitian semu (quasi eksperimen). Dengan Desain yang digunakan dalam penelitian adalah Pretest-Posttest Control Group Design. Populasi yang digunak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 1 publication
0
6
0
15
Order By: Relevance
“…Puspitasari et al (2018) found that the use of instructional media significantly influenced students' motivation. Meanwhile, if online learning with the Edmodo application continued to be done, student achievement would increase, and the teacher would also save time and energy in the learning process (Sobron et al, 2019). Table 7 showed that most of the learning devices used by lecturers in the classroom were PCs or laptops connected to the internet, projectors (LCD), and smartphones.…”
Section: Highmentioning
confidence: 99%
See 1 more Smart Citation
“…Puspitasari et al (2018) found that the use of instructional media significantly influenced students' motivation. Meanwhile, if online learning with the Edmodo application continued to be done, student achievement would increase, and the teacher would also save time and energy in the learning process (Sobron et al, 2019). Table 7 showed that most of the learning devices used by lecturers in the classroom were PCs or laptops connected to the internet, projectors (LCD), and smartphones.…”
Section: Highmentioning
confidence: 99%
“…This finding was consistent with the results of previous studies that online learning had flexibility in its implementation and was able to encourage social distancing behavior, could reduce the potential for the spread of Covid-19 in the campus environment, and eliminate awkward feelings so students could express ideas, opinions and ask questions freely. Online learning also could provide students with more meaningful learning experiences (Sobron et al, 2019) and provided new experiences more challenging than conventional learning models (Kuntarto, 2017). The results of online learning English studies with complementary media web blogs proved that online learning could improve students' reading skills (Khusniyah & Hakim, 2019).…”
Section: Advantages and Disadvantages Of Online Learning During The Covid-19 Pandemicmentioning
confidence: 99%
“…Sedangkan media gambar merupakan salah satu media yang dapat digunakan untuk penyaluran informasi dan dapat meransang siswa untuk belajar (Yuswanti, 2011). Selain itu media gambar juga berfungsi sebagai menarik dan mengarahkan perhatian siswa untuk berkonsentrasi pada isi pelajaran yang dibahas (Suparman et al, 2020). Hal ini didukung dengan hasil observasi aktivitas siswa dan aktivitas guru yang menunjukkan adanya peningkatan disetiap siklus yakni: hasil obsevasi aktivitas siswa siklus I 63% sedangkan hasil observasi aktivitas guru pada ssiklus I 66,1% dengan predikat cukup, mengalami peningkatan pada siklus II yakni pada observasi aktivitas peserta didik mencapai 81.5% sedangkan observasi aktivitas guru mencapai 95,6% dengan predikat baik.…”
Section: Hasil Dan Pembahasanunclassified
“…The implementation of education is expected to shape students' attitudes, knowledge and skills (Asfiati & Mahdi, 2020;Sobron et al, 2019). SD education environment is an important means of preparing students with excellent potential (Prasetyo, 2017).…”
Section: Introductionmentioning
confidence: 99%